Characterization of vasorelaxant responses to anandamide in the rat mesenteric arterial bed - Harris, David (Blackwell Science Inc, 2002)
The endogenous cannabinoid anandamide has recently been identified as a vasorelaxant but the underlying mechanisms are controversial. The vasorelaxant responses to anandamide have now been examined in the rat mesenteric arterial bed. Anandamide caused potent vasorelaxations (pD(2) = 6.24 ± 0.06; R(max) = 89.4 ± 2.2 %) which were unaffected by inhibition of nitric oxide synthase with N(G)-nitro-l-arginine methyl ester (l-NAME; 300 μm). The responses were also predominantly endothelium independent and were unaffected by the cannabinoid CB(1) receptor antagonist SR141716A (1 μm), although at higher concentrations (3 and 10 μm) SR141716A was inhibitory. Both 1 mm ouabain (pD(2) = 5.90 ± 0.07; R(max) = 50.4 ± 6.5 %) and 100 μm 18α-glycyrrhetinic acid (pD(2) = 6.04 ± 0.14; R(max) = 40.9 ± 5.8 %) opposed anandamide-induced vasorelaxation. However, the gap junction inhibitors carbenoxolone (100 μm) and palmitoleic acid (50 μm) did not affect vasorelaxation to anandamide. Relaxation to anandamide was significantly attenuated by both capsaicin pretreatment to deplete the sensory nerves of neurotransmitters (pD(2) = 5.86 ± 0.18; R(max) = 56.3 ± 5.2 %) and the vanilloid antagonist ruthenium red (10 μm; pD(2) = 5.64 ± 0.09; R(max) = 33.7 ± 3.9 %). However, these inhibitory effects were prevented by the additional presence of l-NAME, when the relaxation to anandamide was unaffected (pD(2) = 6.19 ± 0.07; R(max) = 81.9 ± 2.8 %). The inhibitor of neuronal nitric oxide synthase, 7-nitroindazole, also prevented capsaicin from inhibiting the responses to anandamide. The results of this study point to anandamide acting via several mechanisms, which include the involvement of sensory nerves, but only in the presence of nitric oxide.